2015
DOI: 10.1161/atvbaha.114.303568
|View full text |Cite
|
Sign up to set email alerts
|

Treating Atherosclerosis With Regulatory T Cells

Abstract: Regulatory T cells (Tregs) play an important role in the regulation of T cell-mediated immune responses through suppression of T cell proliferation and secretion of inhibitory cytokines such as IL-10 and TGF-β. Impaired Treg numbers and function have been associated with numerous diseases and an imbalance between pro-inflammatory/pro-atherogenic cells and Tregs promotes atherosclerotic disease. Restoration of this balance by inducing Tregs has great therapeutic potential to prevent cardiovascular disease. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 83 publications
6
139
0
7
Order By: Relevance
“…41). Impaired Treg numbers and function are found in patients with cardiovascular disease compared with healthy controls, and studies in mice indicate that Treg numbers in plaques decline with time of Western diet feeding, resulting in an accumulation of effector T cells that promote atherosclerosis (41). We observed a similar decline in plaque macrophage expression of Aldh1a2 with atherosclerosis progression, suggesting that the loss of this iTreg differentiation signal may contribute to the decline.…”
Section: Mir33supporting
confidence: 53%
See 2 more Smart Citations
“…41). Impaired Treg numbers and function are found in patients with cardiovascular disease compared with healthy controls, and studies in mice indicate that Treg numbers in plaques decline with time of Western diet feeding, resulting in an accumulation of effector T cells that promote atherosclerosis (41). We observed a similar decline in plaque macrophage expression of Aldh1a2 with atherosclerosis progression, suggesting that the loss of this iTreg differentiation signal may contribute to the decline.…”
Section: Mir33supporting
confidence: 53%
“…41). To determine whether inhibition of miR-33 in macrophages could promote Treg differentiation, we cocultured naive T cells with macrophages that were transfected with anti-miR-33 or control oligonucleotides ( Figure 6A).…”
Section: Inhibition Of Mir-33 In Macrophages Promotes Treg Differentimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified subtypes of T cells and macrophages that do not necessarily drive pathogenesis but may mediate healing, likely by primarily eliciting anti-inflammatory responses. 18,19 Regarding the downstream effects of TLR7 activation, two recent studies have implicated TLR7 in the control or abatement of inflammation and in the adaptive immune response in both macrophages 16 and T cells, 17 cell types which are frequently found in atherosclerotic lesions. In an experimental study of airway inflammation, imiquimod promoted the resolution of inflammation by inducing the lipid mediator resolvin D in murine macrophages, 16 an effect that has also been observed in vitro in human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although some high affinity self-recognizing T cells are removed in the thymus by negative selection, it is important to recognize that essentially all T cells in an organism not exposed to pathogens are (positively) selected for self-antigens 132, 133 . The effect of Tregs has been extensively tested in the setting of atherosclerotic disease 134 . From a functional point of view, nT regs are considered anti-inflammatory immune cells, classically defined by co-expression of IL-2 receptor, CD25, the forkhead transcription factor (FoxP)-3, and the co-stimulatory molecule CTLA-4 135 .…”
Section: The Antigen-specific T Cell Orchestrates Plaque Inflammationmentioning
confidence: 99%